Professor Zinaida M Skripnichenko, the founder of Ukrainian ocular traumatology - N. F. Bobrova (Ukrainian Society of Ophthalmologists, 2021)
Ocular injury is always an emergency and sometimes a tragedy for a human being of any age. Our eyes provide us with as much as 90% of the information of the world around us. And, suddenly, one or (less commonly) both of them lose this invaluable capacity most commonly due to a disaster, crash, or wounding, and less commonly due to mischance or negligence. That is why ophthalmologists give much attention to the prevention of ocular injury and treatment and rehabilitation of patients having an injury to a previously healthy globe.